Preparation method of charcoal modified light cement floating type adsorption material

By preparing biochar modified lightweight cement floating adsorption materials, the problem that traditional cement-based materials are difficult to load walnut shell charcoal powder is solved, and efficient adsorption and recycling of walnut shell charcoal powder is achieved, which improves adsorption performance and economic benefits. In line with environmental protection concepts.

CN119281306APending Publication Date: 2025-01-10SOUTHWEST FORESTRY UNIVERSITY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411575965.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Traditional cement-based materials have large density and small pores, making it difficult to load walnut shell charcoal powder, resulting in the failure to effectively recycle and harbor waste in the walnut industry and potential harm to the environment.

Method used

The preparation method of biochar modified lightweight cement floating adsorbent material is prepared by pretreatment of walnut shells, impregnation and roasting of iron nitrate, combined with cement, calcium stearate and polypropylene fibers, and rich pores and good machinery are prepared. A lightweight cement material with performance, capable of loading adsorbents and floating on the water surface.

Benefits of technology

It has achieved efficient adsorption and recycling of walnut shell carbon powder, improved adsorption performance and economic benefits, conformed to environmental protection concepts, promoted sustainable development, and improved the adsorption performance of lightweight cement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281306A_ABST
    Figure CN119281306A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of chemical synthesis, and particularly relates to a preparation method of a biochar modified light cement floating type adsorbing material, which comprises the following steps: pretreating walnut shells, crushing the pretreated walnut shells, sieving with a 60-80-mesh sieve, and taking particulate matters between two sieve plates to obtain walnut shell particles; preparing a ferric nitrate impregnation liquid; the walnut shell particles and the ferric nitrate steeping liquor are contained in a container according to the proportion of Cg: DmL to be stirred, steeped and mixed, then suction filtration separation is conducted, solid separated matter is roasted, products are put into a mortar to be ground, modified walnut shell activated carbon powder is obtained, and the ratio of C: D is 1: 50; the modified walnut shell activated carbon powder is combined with cement, and the charcoal modified light cement floating type adsorption material is prepared. The modified walnut shell activated carbon powder is immobilized on the light cement material, the excellent adsorption performance of the modified walnut shell activated carbon powder is reserved, recycling is facilitated, and resource utilization of waste is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical synthesis, and in particular to a method for preparing a biochar-modified lightweight cement floating adsorption material. Background Art

[0002] In recent years, the use of agricultural waste as raw materials to prepare biochar as an adsorbent has achieved relatively ideal adsorption effects. Walnuts have become a priority economic forest because of their easy management and high return on investment. The market demand for walnut deep-processing products is also growing. However, in the production process of walnut products, a large number of walnut shells are discarded. Most of the large amount of shell waste generated by the walnut industry is regarded as useless and abandoned in the fields. Burning it further deteriorates the ecology. Only a very small amount is recycled for specific industrial purposes, such as adsorbent manufacturing or polishing materials. However, walnut shell charcoal powder is not easy to recycle, resulting in poor economic benefits. At the same time, it will also bring potential harm to the environment if it is scattered in natural water bodies.

[0003] As a traditional building material, cement has the advantages of low cost, strong mechanical properties and wide application range. Solidifying pollutants in industrial wastewater through cement-based materials is one of the mainstream treatment methods. Cement-based solidification or stabilization technology can convert liquid, semi-solid or powdered waste into monolithic or granular materials for transportation and landfill to achieve the purpose of harmlessness. However, traditional cement-based materials have high density, small pores and smooth surface, which are difficult to load walnut shell charcoal powder. Summary of the invention

[0004] In order to overcome the deficiencies of the prior art, the present invention provides a method for preparing a biochar-modified lightweight cement floating adsorption material.

[0005] The present invention is achieved through the following technical solutions.

[0006] The present invention provides a method for preparing a biochar-modified lightweight cement floating adsorption material, comprising the following steps:

[0007] S1: pre-treating the walnut shells, crushing the pre-treated walnut shells, passing through a 60-80 mesh sieve, taking the granular material between two layers of sieve plates, and obtaining walnut shell particles;

[0008] S2: preparing iron nitrate impregnation solution;

[0009] S3: walnut shell particles and ferric nitrate impregnation solution are placed in a container in a ratio of Cg:Dml, stirred and impregnated, the impregnated mixture is filtered and separated, the solid separated product is roasted, and the product is put into a mortar for grinding to obtain modified walnut shell activated carbon powder, wherein C:D=1:50;

[0010] S4: The modified walnut shell activated carbon powder is combined with cement to prepare a biochar-modified lightweight cement floating adsorption material.

[0011] As a further improvement of the above solution, S4 comprises the following steps:

[0012] a1: Weigh cement powder and put it into a mold, weigh calcium stearate, polypropylene fiber, and modified walnut shell activated carbon powder, add them to the cement powder and stir to obtain lightweight cement dry material;

[0013] a2: Add deionized water and 30% hydrogen peroxide solution to the lightweight cement dry material, stir and mix, place in a cool and dry place after stirring and mixing, wait for the cement to automatically dry and form, and obtain a biochar modified lightweight cement floating adsorption material.

[0014] As a further improvement of the above scheme, the pretreatment includes: washing and soaking the walnut shells with tap water to wash away most of the dust and impurities; washing the walnut shells with deionized water to thoroughly clean the impurities on the surface; and drying them in an oven at 110° C. for 24 hours.

[0015] As a further improvement of the above scheme, the concentration of the ferric nitrate impregnation solution is 1 mol / L Fe(NO3)3.

[0016] As a further improvement of the above scheme, the stirring, impregnation and mixing time in S3 is 4 hours; and the roasting condition of the solid separation is roasting in a constant temperature muffle furnace at 200° C. for 2 hours.

[0017] As a further improvement of the above scheme, the modified walnut shell activated carbon powder in S3 is a sieved carbon powder obtained by grinding the roasted product and passing it through a 160-mesh sieve.

[0018] As a further improvement of the above scheme, the cement in S4 is 425 hard cement, the stirring and mixing time in a1 and a2 is 1 minute, and the automatic drying time is 7 days.

[0019] As a further improvement of the above scheme, the cement powder: calcium stearate: polypropylene fiber: modified walnut shell activated carbon powder: deionized water: 30% hydrogen peroxide solution are Eg: Fg: Gg: Hg: JmL: KmL respectively; wherein, E: F: G: H: J: K = 100: 0.38-0.42: 0.38-0.42: 1.4-1.6: 40: 3.8-4.2, and the temperature of the deionized water is 45-55°C.

[0020] As a further improvement of the above scheme, the cement powder: calcium stearate: polypropylene fiber: modified walnut shell activated carbon powder: deionized water: 30% hydrogen peroxide solution are Eg:Fg:Gg:Hg:JmL:KmL respectively; wherein, E:F:G:H:J:K=100:0.4:0.4:1.5:40:4, and the temperature of the deionized water is 50°C.

[0021] The present invention also provides a biochar-modified lightweight cement floating adsorption material prepared by the above preparation method.

[0022] The beneficial effects achieved by the present invention are:

[0023] Compared with the prior art, the raw material walnut shell used in the present invention has a huge output, a stable source of raw materials for walnut shell, a low price, and a low cost. The walnut shell has a large amount of cellulose and pores, is highly aromatic, has well-developed micropores, and has a huge specific surface area. In addition, the particle surface carries a large number of functional groups, such as carboxyl, hydroxyl, phenols, lactones, quinones, ethers, etc., and not only physical adsorption but also chemical adsorption occurs during the adsorption process. Therefore, the preparation of walnut shell carbon adsorbent using walnut shell as raw material is not only more excellent in dye adsorption in terms of material, but also has a far-reaching impact on economic benefits and environmental protection.

[0024] At the same time, compared with conventional ordinary cement, the light cement material prepared by composite addition in the present invention has abundant pores inside, and by adding polypropylene fiber and calcium stearate, it is ensured that it has good mechanical properties under the premise of low density, and can load adsorption catalyst. Lightweight cement has a low density, so it can float on the water surface, and in addition to retaining the original mechanical strength properties of cement, it becomes a multifunctional cement-based adsorption material that can float on the liquid surface and is easy to recycle.

[0025] Immobilizing walnut shell carbon powder on lightweight cement materials can not only retain its excellent adsorption properties, but also facilitate recycling. Combining the floatation, mechanical strength and durability of lightweight cement with the adsorption, filtration and other characteristics of walnut shell carbon, it realizes the resource utilization of waste, conforms to the concept of environmental protection, and helps promote sustainable development. At the same time, it can also improve the adsorption properties of lightweight cement and meet the actual needs of materials with specific functions in specific engineering or environmental applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is an ultraviolet characterization diagram of the adsorption of crystal violet liquid by the biochar-modified lightweight cement floating adsorption material of the present invention;

[0027] Figure 2 This is an infrared characterization diagram of the adsorption of crystal violet liquid by the biochar-modified lightweight cement floating adsorption material in the present invention;

[0028] Figure 3 This is the XRD spectrum of the biochar-modified lightweight cement floating adsorption material in the present invention;

[0029] Figure 4 This is a SEM image of the biochar-modified lightweight cement floating adsorption material of the present invention. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0031] The present invention provides a method for preparing a biochar-modified lightweight cement floating adsorption material, comprising the following steps:

[0032] S1: pre-treat the walnut shells, crush the pre-treated walnut shells, pass them through a 60-80 mesh sieve, take the granular material between the two sieve plates, and obtain walnut shell particles.

[0033] Specifically, the pretreatment includes: washing and soaking the walnut shells with tap water to wash away most of the dust and impurities; washing the walnut shells with deionized water to thoroughly clean the impurities on the surface; and drying them in an oven at 110° C. for 24 hours.

[0034] S2: prepare an iron nitrate impregnation solution, wherein the concentration of the iron nitrate impregnation solution is 1 mol / L Fe(NO3)3.

[0035] S3: Walnut shell particles and ferric nitrate impregnation solution are placed in a container in a ratio of Cg:Dml, stirred and impregnated, the impregnated mixture is separated by suction filtration, the solid separated product is roasted, and the product is put into a mortar for grinding to obtain modified walnut shell activated carbon powder, wherein C:D=1:50.

[0036] Furthermore, the stirring, impregnation and mixing time in S3 is 4 hours; and the calcination condition of the solid separation is calcination in a constant temperature muffle furnace at 200° C. for 2 hours.

[0037] The modified walnut shell activated carbon powder in S3 is a sieved carbon powder obtained by grinding the roasted product and passing it through a 160-mesh sieve.

[0038] S4: The modified walnut shell activated carbon powder is combined with cement to prepare a biochar-modified lightweight cement floating adsorption material.

[0039] Specifically, S4 includes the following steps:

[0040] a1: Weigh cement powder and put it into a mold, weigh calcium stearate, polypropylene fiber, and modified walnut shell activated carbon powder, add them to the cement powder and stir to obtain lightweight cement dry material;

[0041] a2: adding deionized water and 30% hydrogen peroxide solution to the lightweight cement dry material, stirring and mixing, placing in a cool and dry place after stirring and mixing, and waiting for the cement to automatically dry and form, thereby obtaining a biochar-modified lightweight cement floating adsorption material;

[0042] Furthermore, the cement in S4 is 425 hard cement.

[0043] Furthermore, the stirring and mixing time in a1 and a2 is 1 min, and the automatic drying time is 7 days.

[0044] Specifically, cement powder: calcium stearate: polypropylene fiber: modified walnut shell activated carbon powder: deionized water: 30% hydrogen peroxide solution are Eg: Fg: Gg: Hg: JmL: KmL respectively; among which, E: F: G: H: J: K = 100: 0.38-0.42: 0.38-0.42: 1.4-1.6: 40: 3.8-4.2, and the temperature of deionized water is 45-55°C.

[0045] Furthermore, cement powder: calcium stearate: polypropylene fiber: modified walnut shell activated carbon powder: deionized water: 30% hydrogen peroxide solution are Eg: Fg: Gg: Hg: JmL: KmL respectively; wherein, E: F: G: H: J: K = 100: 0.4: 0.4: 1.5: 40: 4, and the temperature of the deionized water is 50°C.

[0046] The present invention also provides a biochar-modified lightweight cement floating adsorption material prepared by the above preparation method.

[0047] Example 1

[0048] S1: Use a balance to weigh 10g of walnut shells in a beaker for later use, wash and soak the walnut shells with tap water to wash away most of the dust and impurities; wash the walnut shells with deionized water to thoroughly clean the impurities on the surface; put them in an oven at 110°C and dry them for 24 hours; use a grinder to crush the dried walnut shells, pass them through a 60-80 mesh sieve, and take the granular material between the two layers of sieve plates to obtain walnut shell particles.

[0049] S2: preparing a ferric nitrate impregnation solution.

[0050] Use an analytical balance to accurately weigh 40.40g of solid ferric nitrate nonahydrate into a clean and dry 100mL beaker, add 50mL of deionized water to dissolve, and after complete dissolution, transfer to a 100mL volumetric flask, wash the beaker and glass rod with a small amount of deionized water, and make up to 100mL of 1mol / L Fe(NO3)3 solution, where the mass ratio of ferric nitrate nonahydrate to deionized water is: 40.400g / 75.952g, and the mass volume ratio of ferric nitrate nonahydrate to deionized water is: 40.400g / 759.524mL. Transfer 100mL of 1mol / L Fe(NO3)3 solution to a clean and dry 250mL beaker with a glass rod.

[0051] S3: Use an analytical balance to accurately weigh 2 g of the walnut shell particles prepared in S1, add it to a 250 mL beaker filled with 100 mL of 1 mol / L Fe(NO3)3 impregnation solution, and use a magnetic stirrer to stir the impregnation mixture at room temperature for 4 hours. After the impregnation mixture is separated by suction, the solid separate is placed in a muffle furnace and calcined at 200°C in anoxic conditions for 2 hours. The calcined product is placed in a mortar and ground into powder, and passed through a 160-mesh sieve to obtain modified walnut shell activated carbon powder.

[0052] S4 combines modified walnut shell activated carbon powder with cement:

[0053] a1: Use an analytical balance to accurately weigh 100g of cement powder, which is 425 hard cement, and put the cement powder into a cylindrical plastic mold. Use an analytical balance to accurately weigh 0.4g of calcium stearate, 0.4g of polypropylene fiber, and 1.5g of modified walnut shell activated carbon powder on weighing paper, add them to the cement powder, and stir and mix for 1 minute to obtain lightweight cement dry material;

[0054] a2: Use a measuring cylinder to accurately measure 100 mL of deionized water in a clean and dry 250 mL beaker, heat the deionized water to 60°C with an electric furnace, use a measuring cylinder to accurately measure 40 mL of 60°C deionized water and add it to the lightweight cement dry material, use a pipette to accurately measure 4 mL of 30% hydrogen peroxide solution and add it to the lightweight cement dry material, stir and mix the raw materials, and the stirring and mixing time is 1 min. The stirring and mixing time determines the foaming effect of the cement. If the time is too short, it will not be fully mixed. If the time is too long, most of the bubbles will be discharged and a good foaming effect cannot be achieved. Therefore, 1 min is preferred. After stirring and mixing, place it in a cool and dry place for 7 days until the cement automatically dries and forms, and obtains a biochar-modified lightweight cement floating adsorption material.

[0055] The prepared biochar-modified lightweight cement floating adsorption material is dark gray, with a mass of 111.06 g, a height of 4.75 cm, and an upper surface area of ​​42.75 cm. 2, density is 0.5469g / cm 3 , can withstand a maximum pressure of 119N / cm 2 .

[0056] It should be noted that the biochar-modified lightweight cement floating adsorption material selected in the present invention needs to have a relatively low density and be able to withstand a certain external pressure.

[0057] Example 2

[0058] The difference from Example 1 is that the amount of H2O2 added is 3.5 mL, and the density of the prepared material is 0.6187 g / cm 3 The maximum pressure it can withstand is 126.74N / cm 2 .

[0059] Example 3

[0060] The difference from Example 1 is that the amount of H2O2 added is 4.5 mL, and the density of the prepared material is 0.4033 g / cm 3 The maximum pressure it can withstand is 47.24N / cm 2 .

[0061] Combining Example 1, Example 2 and Example 3, it can be seen that the amount of H2O2 added has a great influence on the performance of the material. Compared with the three, the biochar-modified lightweight cement floating adsorption material prepared when the amount of H2O2 added is 0.4 mL has a lower density and higher compressive resistance, which is more in line with actual needs.

[0062] Example 4

[0063] The difference from Example 1 is that the amount of calcium stearate added is 0.3 g, and the density of the prepared material is 0.6976 g / cm 3 The maximum pressure it can withstand is 174.95N / cm 2 .

[0064] Example 5

[0065] The difference from Example 1 is that the amount of calcium stearate added is 0.5 g, and the density of the prepared material is 0.5714 g / cm 3 The maximum pressure it can withstand is 117.32N / cm 2 .

[0066] Combining Example 1, Example 4 and Example 5, it can be seen that the amount of calcium stearate added has a great influence on the performance of the biochar modified lightweight cement floating adsorption material. If the amount is too little, the bubbles formed by hydrogen peroxide inside the cement cannot be evenly filled inside the cement. If the amount is too much, it will react with hydrogen peroxide and eventually cause the collapse of the pores inside the lightweight cement, thereby increasing the density and making it difficult to float. Compared with the three, the biochar modified lightweight cement floating adsorption material prepared when the amount of calcium stearate added is 8 mL has a lower density and higher compressive resistance, which is more in line with actual needs.

[0067] Example 6

[0068] The difference from Example 1 is that the deionized water temperature is 25°C and the density of the prepared material is 1.1229 g / cm 3 The maximum pressure it can withstand is 172.98N / cm 2 .

[0069] Example 7

[0070] The difference from Example 1 is that the deionized water temperature is 70°C and the density of the prepared material is 52.28 g / cm 3 The maximum pressure it can withstand is 0.4335N / cm 2 .

[0071] In combination with Example 1, Example 6 and Example 7, it can be seen that the deionized water temperature has a great influence on the performance of the biochar modified lightweight cement floating adsorption material. The preparation temperature affects the reaction rate of H2O2 and the slurry molecules. When the temperature is low, the H2O2 molecules in the cement react slowly with the cement slurry molecules, and fewer bubbles are generated. The density of the cement is large and it is difficult to float. When the preparation temperature is too high, the H2O2 molecules in the cement react violently with the cement slurry molecules, and the pores inside the cement increase. Therefore, as the water temperature increases, the density of the prepared material decreases, and the compressive resistance decreases. Compared with the three, the biochar modified lightweight cement floating adsorption material prepared when the deionized water temperature is 70°C has a lower density and a higher compressive resistance.

[0072] Example 8

[0073] The difference from Example 1 is that the concentration of the ferric nitrate impregnation solution is 0.8 mol / L Fe(NO3)3, 0.2 g of modified walnut shell activated carbon powder is used to adsorb 100 mL of 20 mg / L crystal violet, and the adsorption rate in 60 min is 86.28%.

[0074] Example 9

[0075] The difference from Example 1 is that the concentration of the ferric nitrate impregnation solution is 1.2 mol / L Fe(NO3)3, 0.2 g of modified walnut shell activated carbon powder is used to adsorb 100 mL of 20 mg / L crystal violet, and the adsorption rate in 60 min is 89.01%.

[0076] Under the same conditions as in Example 8 and Example 9, the adsorption rate of 100 mL of 20 mg / L crystal violet by the modified walnut shell activated carbon powder obtained by using 1.0 mol / LFe(NO3)3 was 91.92%. Under the same conditions, the adsorption rate of the unmodified walnut shell carbon powder was 44.11%.

[0077] From the above comparison, it can be seen that Fe(NO3)3 modification can make walnut shell carbon Fe-modified, thus -1 The Fe-OC structure is formed at the walnut shell carbon, thereby promoting the adsorption of dyes by walnut shell carbon. The modified walnut shell activated carbon powder obtained with a Fe(NO3)3 concentration of 1.0 mol / L has the best effect.

[0078] Further analysis was performed on the liquid ultraviolet characterization of the adsorption of crystal violet by the biochar-modified lightweight cement floating adsorbent material prepared in Example 1 (see Figure 1 ), where a, b, c, d, e, f, g, h, i represent the liquid UV absorption spectra of 20 mg / L crystal violet adsorbed by biochar-modified lightweight cement floating adsorbent material for 0, 10, 20, 30, 40, 50, 60, 70, 80 min. Figure 1 It can be seen that within the time range of 0-80min, as the reaction time increases, the maximum adsorption peak intensity of crystal violet gradually decreases. When the adsorption time reaches 80min, the crystal violet adsorption peak decreases slowly, which indicates that the adsorption of crystal violet by biochar-modified lightweight cement floating adsorption material has reached adsorption saturation state.

[0079] Further analysis, infrared analysis was performed on the material prepared in Example 1, as shown in Figure 2 As shown, Figure 2 a is crystal violet, b is biochar modified lightweight cement floating adsorption material, and c is biochar modified lightweight cement floating adsorption material adsorbing crystal violet. Figure 2 It can be seen that at 442cm -1 、877cm -1 、1004cm -1 、1417cm -1 and 3631cm -1There are typical infrared vibration peaks nearby, which are respectively attributed to the infrared vibration peaks of Fe-O bond in iron oxide, deformation of benzene ring CH face, CN, CH deformation and -OH. This indicates that there are hydroxyl groups, iron oxides, aromatic rings and N-containing compounds on the surface of biochar modified lightweight cement floating adsorption material. After adsorption of crystal violet, 3631cm -1 The peak spacing at 3631 cm -1 The free -OH at the site formed a hydrogen bond with the oxygen in the crystal violet. After the biochar-modified lightweight cement floating adsorbent material adsorbed crystal violet, the infrared peak became broader and stronger, indicating that the crystal violet was adsorbed on the biochar-modified lightweight cement floating adsorbent material in molecular form.

[0080] In order to investigate the crystal phase characteristics of the prepared materials, XRD characterization analysis was performed. Figure 3 As shown, Figure 3 Among them, a is walnut shell modified lightweight cement, b is lightweight cement, and c is pure cement.

[0081] Among them, lightweight cement is a cement material prepared without adding modified walnut shell activated carbon powder, and other conditions are the same as the preparation conditions of biochar modified lightweight cement floating adsorption material.

[0082] Among them, pure cement is a cement material prepared without adding modified walnut shell activated carbon powder and H2O2, and other conditions are the same as the preparation conditions of biochar-modified lightweight cement floating adsorption material.

[0083] Depend on Figure 3 It can be seen that the peak values ​​of lightweight cement and pure cement are basically unchanged. This is because the preparation of lightweight cement does not use crystalline materials, while the floating adsorption material of biochar-modified lightweight cement has a sharp derivative peak at 2θ=26.12°. At the same time, there are certain shifts and changes at 2θ=17.54°, 23.79°, and 56.45°, indicating that since lightweight cement is loaded with walnut shell charcoal modified by Fe(NO3)3, there is iron doping in the floating adsorption material of biochar-modified lightweight cement, which leads to the left shift of the diffraction peak of the floating adsorption material of biochar-modified lightweight cement and the increase of the interlayer spacing.

[0084] The prepared materials were further subjected to SEM analysis, such as Figure 4 As shown. In the figure, a, b, c, and d are the SEM images of walnut shell charcoal, lightweight cement, biochar modified lightweight cement floating adsorption material, and biochar modified lightweight cement floating adsorption material adsorbing crystal violet. Figure 4It can be seen that walnut shell charcoal has a significant pore structure, while lightweight cement is relatively loose, with a large number of dense and irregular protrusions and more pores. When the modified walnut shell activated carbon and lightweight cement are combined, there are still obvious pores and a significant lamellar structure, which leads to better adsorption performance. The SEM image of the biochar-modified lightweight cement floating adsorption material after adsorption of crystal violet shows that compared with before adsorption, the surface of the material after adsorption of crystal violet has significantly fewer irregular protrusions and holes, which may be due to the adsorption of crystal violet on the surface of walnut shell charcoal-modified lightweight cement. The above characterization data confirm the structural factors that the biochar-modified lightweight cement floating adsorption material has excellent crystal violet adsorption performance.

[0085] The above describes in detail the implementation modes of the present invention in conjunction with the accompanying drawings, but the present invention is not limited to the above implementation modes. The implementation modes can still be changed within the knowledge scope of ordinary technicians in the field. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a biochar-modified lightweight cement floating adsorption material, comprising the following steps: S1: pre-treating the walnut shells, crushing the pre-treated walnut shells, passing through a 60-80 mesh sieve, taking the granular material between two layers of sieve plates, and obtaining walnut shell particles; S2: preparing iron nitrate impregnation solution; S3: walnut shell particles and ferric nitrate impregnation solution are placed in a container in a ratio of Cg:Dml, stirred and impregnated, the impregnated mixture is filtered and separated, the solid separated product is roasted, and the product is put into a mortar for grinding to obtain modified walnut shell activated carbon powder, wherein C:D=1:50; S4: The modified walnut shell activated carbon powder is combined with cement powder to prepare a biochar-modified lightweight cement floating adsorption material.

2. According to the method for preparing a biochar-modified lightweight cement floating adsorption material according to claim 1, S4 specifically comprises the following steps: a1: Weigh cement powder and put it into a mold, weigh calcium stearate, polypropylene fiber, and modified walnut shell activated carbon powder, add them to the cement powder and stir to obtain lightweight cement dry material; a2: Add deionized water and 30% hydrogen peroxide solution to the lightweight cement dry material, stir and mix, place in a cool and dry place after stirring and mixing, wait for the cement to automatically dry and form, and obtain a biochar modified lightweight cement floating adsorption material.

3. The method for preparing a biochar-modified lightweight cement floating adsorption material according to claim 1, wherein the pretreatment comprises: Wash and soak the walnut shells with tap water to remove most of the dust and impurities; wash the walnut shells with deionized water to thoroughly clean the impurities on the surface; Place in oven and dry at 110℃ for 24h.

4. The method for preparing a biochar-modified lightweight cement floating adsorption material according to claim 1, characterized in that: The concentration of the ferric nitrate impregnation solution is 1 mol / L Fe(NO3)3.

5. The method for preparing a biochar-modified lightweight cement floating adsorption material according to claim 1, characterized in that: The stirring, impregnation and mixing time in S3 is 4 hours; the solid separation is calcined in a muffle furnace at a constant temperature of 200° C. for 2 hours.

6. The method for preparing a biochar-modified lightweight cement floating adsorption material according to claim 1, characterized in that: The modified walnut shell activated carbon powder in S3 is a sieved carbon powder that is ground from a roasted product and passed through a 160-mesh sieve.

7. The method for preparing a biochar-modified lightweight cement floating adsorption material according to claim 2, characterized in that: The cement in S4 is 425 hard cement, the stirring and mixing time in a1 and a2 is 1 minute, and the automatic drying time is 7 days.

8. The method for preparing a biochar-modified lightweight cement floating adsorption material according to claim 2, characterized in that: The cement powder: calcium stearate: polypropylene fiber: modified walnut shell activated carbon powder: deionized water: 30% hydrogen peroxide solution are Eg: Fg: Gg: Hg: JmL: KmL respectively; wherein, E: F: G: H: J: K = 100: 0.38-0.42: 0.38-0.42: 1.4-1.6: 40: 3.8-4.2, and the temperature of the deionized water is 45-55°C.

9. The method for preparing a biochar-modified lightweight cement floating adsorption material according to claim 8, characterized in that: The cement powder: calcium stearate: polypropylene fiber: modified walnut shell activated carbon powder: deionized water: 30% hydrogen peroxide solution are Eg: Fg: Gg: Hg: JmL: KmL respectively; wherein, E: F: G: H: J: K = 100: 0.4: 0.4: 1.5: 40: 4, and the deionized water temperature is 50°C.

10. The biochar-modified lightweight cement floating adsorption material prepared according to the preparation method of any one of claims 1 to 9.